2013
DOI: 10.1523/jneurosci.4205-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Unstable Representation of Sound: A Biological Marker of Dyslexia

Abstract: Learning to read proceeds smoothly for most children, yet others struggle to translate verbal language into its written form. Poor readers often have a host of auditory, linguistic, and attention deficits, including abnormal neural representation of speech and inconsistent performance on psychoacoustic tasks. We hypothesize that this constellation of reading-related deficits arises from the human auditory system failing to respond to sound in a consistent manner, and that this inconsistency impinges upon the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
250
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(269 citation statements)
references
References 43 publications
10
250
2
1
Order By: Relevance
“…The consistency of neural responses to sound tracks with language skills, suggesting that stable perceptual encoding is vital for the acquisition and maintenance of phonological categories (73). Response consistency peaks in childhood (∼8-11 y of age), declining steadily until young adulthood (24,25); we show that this adolescent decline is mitigated by in-school music lessons.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The consistency of neural responses to sound tracks with language skills, suggesting that stable perceptual encoding is vital for the acquisition and maintenance of phonological categories (73). Response consistency peaks in childhood (∼8-11 y of age), declining steadily until young adulthood (24,25); we show that this adolescent decline is mitigated by in-school music lessons.…”
Section: Discussionmentioning
confidence: 63%
“…Subcortical response consistency peaks in childhood, waning into young adulthood (24), coinciding with a period when learning a second language becomes more difficult than earlier in life (72). Response consistency tracks with language skills (73) and is enhanced in musicians (59,70). Accordingly, we predicted that music training in adolescence prolongs this period of heightened auditory stability.…”
mentioning
confidence: 93%
“…The paradigm also could be useful for examining the frequency-specificity of variations in speech ABR characteristics that have been observed in certain clinical populations (Anderson et al 2010b(Anderson et al , 2012Hornickel et al 2009Hornickel et al , 2013Song et al 2011). Such information could help to elucidate the underlying mechanisms that link the speech ABR to indexes of speech-in-noise perception and speech-and language-related deficits in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities in the speech ABR have been repeatedly correlated with deficits in speech-in noise perception, particularly in aging populations (Anderson et al 2011(Anderson et al , 2012Ruggles et al 2012) and in children, usually with language-related learning problems (Anderson et al 2010b;Hornickel et al 2011;Hornickel and Kraus 2013). A peripheral basis for these abnormalities in terms of hearing sensitivity has generally been ruled out, because the participant groups tested presented clinically normal audiograms.…”
mentioning
confidence: 99%
“…Moreover, since memory traces are formed faster for familiar speech sounds than for other sounds [16] attenuated MMN amplitudes may also reflect the differential mechanisms in the dynamics of short-term memory trace formation for non-speech and speech sounds. Furthermore, recently it has been suggested that weaker stability at the brainstem could lead to deficits in how cortical neurons adapt to sound repetition in children with dyslexia [17]. Thus, further research onto the neural mechanisms underlying attenuated MMN responses in SLI or dyslexia is warranted.…”
Section: Introductionmentioning
confidence: 99%